2022
DOI: 10.1111/cas.15662
|View full text |Cite
|
Sign up to set email alerts
|

LPLUNC1 reduces glycolysis in nasopharyngeal carcinoma cells through the PHB1‐p53/c‐Myc axis

Abstract: Cancer cells usually prefer glycolysis to support their proliferation. Our previous studies have shown that the long palate, lung, and nasal epithelial cell clone 1 (LPLUNC1) can up-regulate prohibitin 1 (PHB1) expression to inhibit the proliferation of nasopharyngeal carcinoma (NPC) cells. Given that PHB1 is an important regulator of cell energy metabolism, we explored whether and how LPLUNC1 regulated glucose glycolysis in NPC cells. LPLUNC1 or PHB1 over-expression decreased glycolysis and increased oxidativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 64 publications
(191 reference statements)
1
2
0
Order By: Relevance
“…However, the roles of the ARHGAP44 / p53 and C-Myc / Cyclin D1 pathways in osteosarcoma remain unclear. The present study revealed that C-myc and Cyclin D1 may be inhibited by the downregulation of ARHGAP44 and upregulation of p53 expression levels, which is consistent with the findings of Oyang and Yenmis et al [ 33 , 34 ]. These results suggest that the downregulation of ARHGAP44 expression may inhibit the proliferation, invasion, and migration of osteosarcoma tumor cells through the p53 / C-myc / Cyclin D1 pathway (Fig.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…However, the roles of the ARHGAP44 / p53 and C-Myc / Cyclin D1 pathways in osteosarcoma remain unclear. The present study revealed that C-myc and Cyclin D1 may be inhibited by the downregulation of ARHGAP44 and upregulation of p53 expression levels, which is consistent with the findings of Oyang and Yenmis et al [ 33 , 34 ]. These results suggest that the downregulation of ARHGAP44 expression may inhibit the proliferation, invasion, and migration of osteosarcoma tumor cells through the p53 / C-myc / Cyclin D1 pathway (Fig.…”
Section: Discussionsupporting
confidence: 93%
“…There is also a regulatory relationship between p53 , C-myc , and Cyclin D1 . Oyang et al [ 33 ] found that LPLUNC1 reduces the proliferation of nasopharyngeal carcinoma tumor cells through the p53 / C-myc pathway. In breast cancer, metformin reduces the expression of Cyclin D1 by upregulating the p53 expression, thereby promoting tumor apoptosis [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…5 C, TOM40 knockdown decreased the levels of phosphorylated AKT, mTOR, p70S6K, pS6 and 4E-BP1, suggesting inactivation of the AKT/mTOR signaling pathway. The p53/p21 pathway acts downstream of ROS signaling in NPC cells and is known to trigger apoptosis [ 16 , 22 ]. We found that inhibition of TOM40 increased p21 and p53 levels, along with that of cleaved PARP and cleaved caspase 3, which lie downstream of p53 signaling.…”
Section: Resultsmentioning
confidence: 99%